PENGAKUAN, PENGUKURAN, PENYAJIAN DAN PENGUNGKAPAN DANA NON HALAL PADA LAPORAN KEUANGANBAZNAS PROVINSI SULAWESI TENGGARA - Asni, Nur; Abdullah, Muntu; Chulhair, Mifta (JURNAL AKUNTANSI DAN KEUANGAN, 2018)
ABSTRACTThis study investigated the accounting treatment Non Halal Fund in BAZNAS Southeast Sulawesi Province has been referring to PSAK 109. The method of data analysis used is descriptive analysis method. The results of this study indicate that the financial statements of BAZNAS Southeast Sulawesi Province not has been referring to PSAK 109. BAZNAS Southeast Sulawesi Province recognizes the acceptance of non halal funds as additional non halal funds account and is presented separately from zakat, infaq and alms funds. presentation of financial statements by BAZNAS of Southeast Sulawesi Province has not been in accordance with PSAK 109. BAZNAS of Southeast Sulawesi Provincehas revealed the existence and policy on the acceptance and distribution of non halal funds. However BAZNAS of Southeast Sulawesi Province has not revealed the amount of non halal fund distribution.Â Keywords: Accounting Treatment, Non Halal Fund, PSAK 109